ANALISIS KARAKTERISTIK INOVASI SISTEM LAYANAN PERIZINAN TERPADU (SILAT) DALAM PERIZINAN REKLAME PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA BEKASI - Faradila Hestiyana; Maesaroh Maesaroh; Nina Widowati (Journal of Public Policy and Management Review, 2023)
Public service problems are something that cannot be avoided by the people of Bekasi City. Advertising permits are the permits most widely accessed by the public in DPMPTSP Bekasi City and each year it always increases. However, the community considers that the services provided related to the issuance of advertising permits are still not satisfactory to the community. Complaints from the public are regarding the difficulty of registering an account at SILAT, frequent interruptions at SILAT, as well as maintenance which tend to often hinder people who want to take care of licensing through SILAT. This study aims to analyze the characteristics of the Sistem Layanan Perizinan Terpadu (SILAT) innovation in advertising licensing at DPMPTSP Bekasi City and to find out the supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. SILAT's innovation in advertising licensing is seen through relative advantage, compatibility, complexity, triability, and observability. In practice, advertising licensing through SILAT has been going well although there are still obstacles regarding its implementation. There are supporting factors for the SILAT innovation in advertising licensing, namely good leadership, DPMPTSP Bekasi City employees who have attended training, and technology that continues to be developed. While the inhibiting factor is the lack of competent employees in terms of risk management.